Immunotherapy Approaches Targeting the Tumor Microenvironment - Usman Haider; Tauseef Abbas (Indus Journal of Bioscience Research, 2023)
Cancer immunotherapy has revolutionized the landscape of cancer treatment by harnessing the power of the immune system to combat malignant tumors. One of the critical factors in the success of immunotherapy is the tumor microenvironment (TME), a complex milieu of cells and molecules that surrounds and interacts with cancer cells. This paper delves into the multifaceted aspects of the TME and explores various immunotherapy approaches aimed at modulating and targeting the TME to enhance anti-tumor immune responses. We discuss the role of immune checkpoint inhibitors, adoptive cell therapies, cytokine-based therapies, and innovative strategies in reprogramming the TME to improve cancer treatment outcomes. Furthermore, we examine the challenges and future directions in the field of immunotherapy targeting the TME.